Digital Implementation of Oscillatory Neural Network for Image Recognition Applications - Abernot, Madeleine; Gil, Thierry; Jiménez, Manuel; Núñez, Juan; Avellido, María J.; Linares-Barranco, Bernabé; Gonos, Théophile; Hardelin, Tanguy; Todri-Sanial, Aida (Frontiers in Neuroscience, 2021)
Computing paradigm based on von Neuman architectures cannot keep up with the ever increasing data growth (also called ”data deluge gap”). This has resulted in investigating novel computing paradigms and design approaches at all levels from materials to system level implementations and applications. An alternative computing approach based on artificial neural networks uses oscillators to compute or Oscillatory Neural Networks (ONNs). ONNs can perform computations efficiently and can be used to build a more extensive neuromorphic system. Here, we address a fundamental problem: can we efficiently perform artificial intelligence applications with ONNs? We present a digital ONN implementation to show a proof-of-concept of the ONN approach of ”computing-in-phase” for pattern recognition applications. To the best of our knowledge, this is the first attempt to implement an FPGA-based fully-digital ONN. We report ONN accuracy, training, inference, memory capacity, operating frequency, hardware resources based on simulations and implementations of 5x3 and 10x6 ONNs. We present the digital ONN implementation on FPGA for pattern recognition applications such as performing digits recognition from a camera stream. We discuss practical challenges and future directions in implementing digital ONN.